Pengaruh Kampanye Hijau “Tumblr Day” terhadap Minat Beli Melalui Brand Trust pada Konsumen Starbucks Coffee (Studi Kasus pada Konsumen Starbucks Coffee di Kota Bandung) - Nabilaah, Jihan; Nurtjahjadi, Edi (J-MAS (Jurnal Manajemen dan Sains), 2024)
The development of the business world in Indonesia is growing, seeing more and more types of businesses and industries emerging, one of which is in the food and beverage sector. Apart from that, the trend of drinking coffee is also increasing. However, the percentage index for Starbucks Coffee experienced a decline in the 2021-2023 period, while its competitors actually experienced an increase in the same year period. This indicates a decrease in buying interest in Starbucks Coffee. The aim of this research is to determine the effect of the green campaign "Tumblr Day" on purchase intention through brand trust among Starbucks Coffee consumers in Bandung City. The type of research used in this research is quantitative approach method. The population taken was Starbucks Coffee consumers who live in the city of Bandung with a total sample of 120 respondents taken using the purposive sampling method. The data analysis technique used is simple and multiple regression tests using SPSS 26 version and using the Sobel test. The research results show that the green campaign "tumblr day" has a positive effect on brand trust. Then, the green campaign "tumblr day" had a positive effect on purchase intention. Brand trust has a positive effect on purchase intention. Brand trust mediates the influence of the green campaign "Tumblr Day" on purchase intention.